Penguatan Usaha Mikro bagi Perempuan Wirausaha Penerima Program Keluarga Harapan di Kota Jambi - Besse Wediawati; Sumarni Sumarni; Idham Khalik; Zulfina Adriani; Dian Mala Fitriani (Jurnal Surya Masyarakat, 2022)
This activity aims to help female micro-entrepreneurs who are recipients of the  Program Keluarga Harapan solve their problems in their business so that they can proceed towards graduation. The problems faced are the entrepreneurial spirit which sometimes fluctuates, especially during a pandemic; limited capital to increase business volume; limited knowledge of business management, as well as low access/utilization of technology to support business. The solution for solving this problem is to provide business strengthening through entrepreneurship training, digital marketing and assistance for the formation of joint business groups. Training and mentoring are carried out using participant and project based learning methods as well as mentoring. The activity was carried out for 6 months, starting from May to October 2021. The team consisted of 5 people with relevant fields of expertise. The result of this activity is an increase in the entrepreneurial spirit, knowledge and empowerment of PPM partners so that they can improve their Culinary Business and progress towards graduation.